\(3\sqrt{3}-2\sqrt{2}=\sqrt{27}-\sqrt{8}>\sqrt{25}-\sqrt{9}=5-3\)
\(\Rightarrow3\sqrt{3}-2\sqrt{2}>2\)
\(3\sqrt{3}-2\sqrt{2}=\sqrt{27}-\sqrt{8}>\sqrt{25}-\sqrt{9}=5-3\)
\(\Rightarrow3\sqrt{3}-2\sqrt{2}>2\)
So sánh M = \(\sqrt{2+\sqrt{5}}\) và N = \(\dfrac{\sqrt{5}+1}{\sqrt{3}}\)
So sánh:
a. 4 và \(2\sqrt{3};\) b. \(-\sqrt{5}\) và -2.
so sánh :
\(2+\sqrt{2}\) và \(3-\sqrt{3}\)
So sánh (không dùng bảng số hay máy tính bỏ túi )
a) \(\sqrt{2}+\sqrt{3}\) và \(\sqrt{10}\)
b) \(\sqrt{3}+2\) và \(\sqrt{2}+\sqrt{6}\)
c) \(16\) và \(\sqrt{15}.\sqrt{17}\)
d) \(8\) và \(\sqrt{15}+\sqrt{17}\)
rút gọn A=\(\dfrac{2a\sqrt{a}+2\sqrt{a}-3a-3}{2\sqrt{a}-3}\)
B =\(\dfrac{2a^2-2a}{\sqrt{a^3}-\sqrt{a}}\)
rồi so sánh
So sánh 3√2 và 2√16. 1/4√12 và 6√1/7
Không dùng MTBT hãy so sánh ; A =\(\frac{19-5\sqrt{3}}{3}\)và B = \(2\sqrt{2}\)
Không dùng MTBT hãy so sánhA = \(\sqrt{\frac{19-5\sqrt{3}}{3}}\)và B = \(2\sqrt{2}\)
so sánh
a. √3+√5 và √17
b. √5+2 và √3+6
c.√2004+√2006 và 2√2005